Biopreservation Potential of Shimeji (Hypsizygus sp.) Mushroom Fermented with Bifidobacterium sp. InaCC B723 - Maskuri, Hafidz Azhar; Aramsirirujiwet, Yaovapa; Kimkong, Ingorn; Darmasiwi, Sari (Biosaintifika: Journal of Biology & Biology Education, 2025)
Nowadays, mushrooms are widely consumed as a source of functional food and health, including the shimeji (Hypsizygus sp) mushroom. Fresh shimeji is highly perishable, mainly due to its high-water content, high respiration rate, and the presence of microflora. The objective of this research was to examine the potential of Bifidobacterium sp. as a starter for fermentation and bio preservation of Hypsizygus sp. In this study, Hypsizygus sp. was fermented with addition of Bifidobacterium sp. (107 CFU/ml), continued with incubation in room temperature 25±2 ̊C for 18 days. Fermented samples were then analyzed for the number of microbial populations including lactic acid bacteria (LAB), yeast, and Enterobacteriaceae using Total Plate Count; chemical quality of pH, lactic acid using titration, nitrite using spectrophotometry, and volatile compounds using GC-MS. During fermentation, the LAB population increased rapidly until it reached its peak population on the 3rd day. The rapid growth of LAB was followed by an increase in lactic acid content and a decrease in pH. Organic acids can control the growth of other microorganisms such as yeasts, molds, and Enterobacteriaceae while preventing the damage and decay of mushrooms. GC-MS analysis of fermented mushroom extract exhibited major bioactive compounds of butanoic acid (14,25%), Hydroperoxide, 1-methylpentyl (10,01%), and n-hexadecanoid acid (9,756%). This research was the first report on the use of Bifidobacterium sp. for Hypsizygus sp. fermentation, with potential to be applied as a bio-preservation method of edible mushrooms with enhanced characteristics which can be applied to the wider community.